Cancer metabolism: a therapeutic perspective - Martinez-Outschoorn, Ubaldo E.; Peiris-Pagés, Maria; Pestell, Richard G.; Sotgia, Federica; Lisanti, Michael P. (Nature reviews. Clinical oncology, 2017)
Key Points The metabolic ecology of tumours enables component cells to generate ATP, maintain redox balance, and undertake biosynthesis, which in turn support tumour progression Tumours share features of complex ecosystems, with cancer cells inducing nutrient enrichment; however, the requirement for a tight nutrient balance might be a vulnerability of tumours that can be exploited therapeutically Compared with their normal counterparts, tumour cells require higher rates of catabolite uptake, transfer, and utilization; hence, catabolite-deprivation might be a selective and effective anticancer treatment strategy Targeting glycolysis and mitochondrial metabolism with drug combinations holds promise as another strategy to disrupt the diverse metabolic compartments within tumours Measuring glucose, lactate, pyruvate, β-hydroxybutyrate, and glutamine levels in different tumour compartments and their intercompartmental transfer is needed in clinical trials that examine the efficacy of drugs targeting tumour metabolism Normal tissues frequently have activation of metabolic pathways that are upregulated in cancer and, therefore, dose-limiting toxicity is a challenge in the development of drugs targeting these pathways Metabolic reprogramming to support tumour growth is a near universal characteristic of cancer, and thus targeting cancer metabolism has been, and continues to be, a focus for drug-development efforts. In this Review, the authors describe the various metabolic alterations and vulnerabilities of tumours that are potentially important targets for anticancer agents, highlighting both the challenges and opportunities. Awareness that the metabolic phenotype of cells within tumours is heterogeneous — and distinct from that of their normal counterparts — is growing. In general, tumour cells metabolize glucose, lactate, pyruvate, hydroxybutyrate, acetate, glutamine, and fatty acids at much higher rates than their nontumour equivalents; however, the metabolic ecology of tumours is complex because they contain multiple metabolic compartments, which are linked by the transfer of these catabolites. This metabolic variability and flexibility enables tumour cells to generate ATP as an energy source, while maintaining the reduction–oxidation (redox) balance and committing resources to biosynthesis — processes that are essential for cell survival, growth, and proliferation. Importantly, experimental evidence indicates that metabolic coupling between cell populations with different, complementary metabolic profiles can induce cancer progression. Thus, targeting the metabolic differences between tumour and normal cells holds promise as a novel anticancer strategy. In this Review, we discuss how cancer cells reprogramme their metabolism and that of other cells within the tumour microenvironment in order to survive and propagate, thus driving disease progression; in particular, we highlight potential metabolic vulnerabilities that might be targeted therapeutically.